Tips on how to collect and administer the mesenchymal stem cell secretome for central nervous system applications - Teixeira, F. G. (2016)
Human mesenchymal stem cells (hMSCs) have been proposed as possible therapeutic agents for central nervous system (CNS) disorders. Recently, it has been suggested that their effects are mostly mediated through their secretome, which contains a number of neuroregulatory molecules capable of increasing cell proliferation, differentiation, and survival in different physiological conditions. Here, we present an overview of the hMSC secretome as a possible candidate in the creation of new cell-free therapies, demonstrating the process of its collection and route of administration, focusing our attention on their effects in CNS regenerative medicine.